2018
DOI: 10.1161/jaha.118.008623
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular Blood Augments Myogenic Constriction of Cerebral Arterioles: Implications for Hemorrhage‐Induced Vasospasm

Abstract: BackgroundSubarachnoid hemorrhage is a serious clinical condition that impairs local cerebral blood flow perfusion and consequently initiates neuronal dysfunction. Pressure‐sensitive myogenic vasomotor regulation is an important mechanism involved in the regulation of cerebral blood flow. We hypothesized that extravascular hemolyzed blood enhances arteriolar myogenic constriction, which in vivo may contribute to the reduction of local cerebral blood flow after subarachnoid hemorrhage.Methods and ResultsArterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Only a handful of studies have utilized cannulated resistance arteries ex vivo to investigate the effects of SAH on myogenic reactivity (Table 1). As demonstrated in mouse olfactory (87,93) and middle cerebral (94), rat parenchymal (95,96) and middle cerebral (97), canine basilar (98), and rabbit cerebellar and posterior cerebral resistance arteries (99,100), these studies are unanimous in concluding that SAH augments cerebral resistance artery myogenic reactivity. Through the use of endothelial denudation (95), smooth muscle cell specific gene deletion (87) and studies on freshly isolated artery myocytes (96,100), this pathological effect can be attributed to a change in smooth muscle cell function.…”
Section: The Myogenic Responsementioning
confidence: 95%
“…Only a handful of studies have utilized cannulated resistance arteries ex vivo to investigate the effects of SAH on myogenic reactivity (Table 1). As demonstrated in mouse olfactory (87,93) and middle cerebral (94), rat parenchymal (95,96) and middle cerebral (97), canine basilar (98), and rabbit cerebellar and posterior cerebral resistance arteries (99,100), these studies are unanimous in concluding that SAH augments cerebral resistance artery myogenic reactivity. Through the use of endothelial denudation (95), smooth muscle cell specific gene deletion (87) and studies on freshly isolated artery myocytes (96,100), this pathological effect can be attributed to a change in smooth muscle cell function.…”
Section: The Myogenic Responsementioning
confidence: 95%
“…As described in a previous study [24], mice were intraperitoneally anesthetized with 4% chloral hydrate (0.4 g/ kg body weight). They were then placed in the stereotaxic apparatus.…”
Section: Sah Model In Micementioning
confidence: 99%
“…Thus, high concentration of ROS (derived from blood) may augment the myogenic tone via directly and indirectly mediate vascular smooth muscle after SAH. Recently, a study from Deng et al (2018) provided direct evidence. They studied the effects of extravascular hemolyzed blood on arteriolar myogenic constriction and found that extravascular hemolyzed blood augments the myogenic constriction of cerebral arterioles, possibly by increasing the vascular production of superoxide.…”
Section: Cerebral Autoregulation Dysfunction After Sahmentioning
confidence: 99%